CREATIVE INDUSTRIES IN THE ARCTIC: A REVIEW OF RUSSIAN SCIENTIFIC LITERATURE - Artur S. Krasil’nikov (Север и рынок: формирование экономического порядка, 2021)
The article reviews the points of view of Russian researchers on the development of creative industries in the Arctic. The main issues that are considered by domestic authors in the works on the development of creative industries in the Russian Arctic are identified, the opinions of the authors on the potential and problems of the development of the Arctic creative industries in the Russian Federation are analyzed. It is concluded that the works of Russian researchers mainly consider such issues as the essence of the concept of “creative industries”, the relevance of the development of Arctic entrepreneurship in the Russian Federation, the prospects for the development of creative industries in the Arctic regions of Russia, the level of development of creative industries as a measure of economic development, potential of creative practice in the Arctic region, issues of forming an active creative class, the attractiveness of the Arctic region for the development of creative industries and key problems of the development of creative industries in the Russian Arctic. According to most authors, the main task of the creative industries in the Russian Arctic is to ensure the dynamic development of small businesses in this macroregion. The potential of creative practice in the Arctic region, from the point of view of domestic authors, lies in the development of tourism and social innovation, as well as in the preservation and reproduction of the national culture of the indigenous peoples of the North and the Arctic. The formation of an active creative class in the region is difficult due to the impact of such factors as the mono-sectoral nature of local economies, a high concentration of capital in the field of environmental management, peripherality and a small number of population. The attractiveness of the Arctic regions for the development of creative industries lies in the unique nature and culture, largely based on the culture of indigenous peoples. Remoteness, transportation challenges, harsh climate, economic ...